Measurement of cross-sections for the (p, xn) reactions in natural molybdenum - Khandaker, Mayeen Uddin; Uddin, M.S.; Kim, K.S.; Lee, Y.S.; Kim, G.N. (Elsevier, 2007)
Cross-sections for the residual radionuclide productions by proton-induced activation on natural molybdenum were measured up to 40 MeV by using a stacked-foil technique at the MC50 cyclotron of the Korea Institute of Radiological and Medical Sciences (KIRAMS). This work has given a new data set for the formation of the investigated radionuclides. The present results for most of the radionuclides showed in general good agreement with the earlier reported data as well as the theoretical data taken from the calculations based on the ALICE-IPPE code. The integral yields for thick targets were also deduced from the measured cross-sections of the produced radionuclides. The optimum production of the Tc-99m radionuclide with minimum impurities can be obtained at the energy ranges from 10 to 23 MeV, where the production yields were obtained as 597.15 MBq mu A(-1)h(-1) at saturation. The measured cross-sections are used for production of medically important radionuclides such as 99mTc, Tc-94m and Tc-93m.g by using the medium-energy cyclotrons. (c) 2007 Elsevier B.V.. All rights reserved.